The Application of the National Land Boundary Law and International Treaties in Domestic Law - Chaoqun Li (Studies in Law and Justice, 2024)
Article 31 of the National Land Boundary Law of the People’s Republic of China stipulates the application of this law and international treaties, which is the technical embodiment of the incorporation of international treaties into domestic law. Through comparison, it is found that, unlike other Chinese laws that directly stipulate that “if this Law has different provisions from international treaties, international treaties shall apply”, Article 31 adopts the concept of “otherwise stipulated”. In this way, the particularity of land boundary and border management affairs is combined with the interpretation of “other provisions”, so as to solve the relationship and application of the Land Boundary Law and international treaties.